REVIEW OF OBSTACLES WHICH INHIBIT ICT ADOPTION IN HIGHER EDUCATION - Samuel NiiBoi Attuquayefio; Hillar Addo (European Scientific Journal, ESJ, 2014)
In view of the important role Information Communication and Technology play in education, most administrators of higher educational institutions have invested into these tools to advance teaching, learning and research. In spite of these huge investments, students, lecturers and administrators are yet to fully adopt these tools. This paper seeks to review obstacles which inhibit adoption of ICT in higher educational institutions. The review identified lack of institutional support, financial support, time to learn new technologies, access to computing, technical support and training. Other obstacles identified were technology reliability, uncertainty about its worth, resistance to change, negative attitude, awareness, relevance, ease of use, attitude of organization, and computer literacy. The article concluded that knowing the extent to which these barriers affect individuals and institutions may help in taking decision on how to tackle them.